Effectiveness of Resilience Soft Skills Training in Improving School Counselors’ Competence for Suicide Prevention - Budi Astuti; Mitta Kurniasari; Rizqi Lestari; Salma Salsabila Hasna; Budi Astuti; Mitta Kurniasari; Rizqi Lestari (Universitas Negeri Malang, 2026)
School counselors play a strategic role in preventing suicidal ideation in high school students. However, limited competence in implementing resilience-based interventions can reduce the effectiveness of counseling services. This study aims to examine the effectiveness of resilience soft skills training in enhancing the competencies of school counselors in suicide prevention. The study used a quantitative, one-group pre-experimental design with a pretest–posttest model. The study subjects consisted of 35 high school counselors in Karanganyar Regency. Data collection was conducted using a structured questionnaire that assessed school counselors' understanding and skills in developing resilience and suicide prevention strategies. The training program was conducted over several sessions, starting with the conceptual basics of resilience, then covering risk factors for suicidal ideation among students, and finally applying resilience-based counseling strategies through discussions and practical exercises. Data were analyzed using a paired-sample t-test. The results of the analysis showed a significant increase in scores between the pretest (M = 53.00) and posttest (M = 80.00), with a t(34) = 20.00 and p < 0.001, as well as a very large effect size (Cohen's d = 3.38). These findings indicate that resilience soft skills training is effective in improving the competence of school counselors in supporting suicide prevention efforts of secondary school students. This study underscores the importance of resilience-based professional development programs for school counselors as an evidence-based approach to supporting student mental health.